Effects of Urea-Ammonium Nitrate Solution on Yield, N2O Emission, and Nitrogen Efficiency of Summer Maize Under Integration of Water and Fertilizer - Ren, Baizhao; Guo, Yanqing; Liu, Peng; Zhao, Bin; Zhang, Jiwang (Frontiers in Plant Science, 2021)
In order to clarify the effects of urea-ammonium nitrate solution (UAN) on yield, nitrogen use efficiency and N2O emissions of summer maize under the condation of water and fertilizer integration, different types of nitrogen fertilizer were selected, namely, ordinary urea (urea) and UAN. Our results showed that the application of UAN was beneficial to improve the dry matter accumulation and distribution of summer maize. Compared with urea treatment, the total nitrogen accumulation of UAN treatment was increased by 15.8%, and the harvest index was increased by 5.5%. The partial productivity, agronomic use efficiency and recovery rate of nitrogen for UAN treatment were also increased by 9.1%, 19.8% and 31.2%, respectively, compared to those of urea treatment. The soil nitrogen dependence rate treated with UAN was significantly decreased by 13.6%, compared to that of urea treatment. In addition, UAN was beneficial to reduce N2O emissions. The N2O warming potential (GWPN2O) and N2O greenhouse gas intensity (GHGIN2O) of urea treatment were 39.3% and 52.4% higher, compared to those of UAN treatment. The improvement of dry matter accumulation and distribution, and nitrogen efficiency for UAN treatment were beneficial to increase grain yield by 9.1%, compared to that of urea treatment. In conclusion, under the fertigation, the application of UAN favors higher yield and nitrogen uptake, with less soil nitrogen residue, higher nitrogen use efficiency, and better environmental effect.